Plan estratégico de desarrollo turístico sostenible para el cantón Pindal, provincia de Loja - Gallardo Ortiz, Yurelis Melina (2015)
The present research proposes the design of a “Strategic Plan for Sustainable Tourism Development in Pindal town, province of Loja”, which begins with the analysis of the parish, as regards of geographical location, environmental conditions (flora-wildlife), statistical data on population, education, housing, health, among others. Next, a diagnostic was made about the tourism potential of the sector, which includes relevant information about tourist facilities, determination de tourism attractions, analysis of tourism demand and zoning of the attractive; they were determined through interviews, surveys, visits in-situ and SWOT analysis. After obtaining the results, I establish strategies based on filing a mission, vision, goals, values, methodological process and strategy development for Pindal. Finally, I prioritized the strategies and worked with that information to set up six programs and twelve projects that are part of the SPSTD, the same that is project to a horizon of seven-year for its development and implementation positioning Pindal as a tourist destination improving the quality of life economy of its population.